Performance Analysis of Flexible Pavement on the Banda Aceh–Medan National Road Using the Pavement Condition Index Method - Isya, Muhammad; Setyawan, Ary; Pillai, Salu S. (Journal of Engineering and Technological Science, 2026)
The Banda Aceh–Medan National Road serves as a strategic transportation corridor in northern Sumatra, supporting regional mobility and economic activities. Continuous traffic loading and environmental effects have caused progressive deterioration of flexible pavement performance along this route. This study aims to evaluate the functional performance of flexible pavement on the Banda Aceh–Medan National Road using the Pavement Condition Index (PCI) method. A quantitative descriptive approach was employed through visual pavement surveys, damage identification, severity classification, and PCI calculation following ASTM D6433 standards. The road section was divided into several sample units to ensure representative condition assessment. The results indicate that the average PCI value of the observed segments falls within the “fair” to “poor” condition categories, with dominant distress types including alligator cracking, rutting, and raveling. Comparative analysis with previous studies confirms the reliability of the PCI method in reflecting actual pavement conditions and supporting maintenance decision-making. The findings emphasize the necessity for timely preventive and corrective maintenance strategies to extend pavement service life. This study contributes empirical evidence for pavement management systems on national roads in Indonesia and reinforces the applicability of PCI as a standardized evaluation tool.